Frequency and coexistence of KRAS, NRAS, BRAF and PIK3CA mutations and occurrence of MMR deficiency in Danish colorectal cancer patients. Issue 2 (6th November 2020) - Poulsen, Tim Svenstrup; de Oliveira, Douglas Vinicius Nogueira Perez; Espersen, Maiken Lise Marcker; Klarskov, Louise Laurberg; Skovrider‐Ruminski, Wojciech; Hogdall, Estrid
Abstract : The MAPK signalling genes KRAS, NRAS and BRAF and the PIK3CA gene are routinely investigated for mutations in the diagnostic routine of colorectal cancer. Few studies have reported co‐existing mutations in these genes with clinical relevance, while some have been previously regarded as mutually exclusive. We set to investigate the frequency and co‐occurrent mutations in these targets, and the occurrence of mismatch repair deficiency (dMMR) in a large cohort of Danish colorectal cancers. 1000 colorectal tumours were sequenced as part of our diagnostic workflow for KRAS, NRAS, BRAF and PIK3CA mutations using next‐generation sequencing (NGS) and analysed by immunohistochemistry (IHC) for loss of the MMR proteins, MLH1, PMS2, MSH2 and MSH6. Co‐existing mutations in 12 patients (1.2%) occurred as multiple mutations in the same gene or spread across several genes ( KRAS, NRAS and/or BRAF ). The frequency of single mutations in the genes occurred with a frequency similar to previously reported, except for a higher frequency of BRAF mutations (18.0%). We found dMMR in 14.6% of the cases with a majority lacking expression of both MLH1 and PMS2. BRAF mutations were only present in dMMR cases involving MLH1 and/or PMS2. Our findings suggest that co‐existing mutations occur, except for the hotspot BRAF V600E, which is mutually exclusive with KRAS/NRAS mutations. Therefore, instead of single gene alterations from the MAPK signalling, assessing co‐occurrence of mutations within one or more of those genes should also be accounted. This may impact future oncological treatments and should be considered in the diagnostic workflow.